ARM-Based Microcontroller Projects Using Mbed - Ibrahim, Dogan (Elsevier Science & Technology, 2019)
ARM-based Microcontroller Projects Using mbed gives readers a good understanding of the basic architecture and programming of ARM-based microcontrollers using ARM’s mbed software. The book presents the technology through a project-based approach with clearly structured sections that enable readers to use or modify them for their application. Sections include: Project title, Description of the project, Aim of the project, Block diagram of the project, Circuit diagram of the project, Construction of the project, Program listing, and a Suggestions for expansion. This book will be a valuable resource for professional engineers, students and researchers in computer engineering, computer science, automatic control engineering and mechatronics.Includes a wide variety of projects, such as digital/analog inputs and outputs (GPIO, ADC, DAC), serial communications (UART, 12C, SPI), WIFI, Bluetooth, DC and servo motorsBased on the popular Nucleo-L476RG development board, but can be easily modified to any ARM compatible processorShows how to develop robotic applications for a mobile robotContains complete mbed program listings for all the projects in the book